Climate changes and wildfire alter vegetation of Yellowstone National Park, but forest cover persists. Issue 1 (25th January 2017) - Clark, Jason A.; Loehman, Rachel A.; Keane, Robert E.
Abstract: We present landscape simulation results contrasting effects of changing climates on forest vegetation and fire regimes in Yellowstone National Park, USA, by mid‐21st century. We simulated potential changes to fire dynamics and forest characteristics under three future climate projections representing a range of potential future conditions using the FireBGCv2 model. Under the future climate scenarios with moderate warming (>2°C) and moderate increases in precipitation (3–5%), model simulations resulted in 1.2–4.2 times more burned area, decreases in forest cover (10–44%), and reductions in basal area (14–60%). In these same scenarios, lodgepole pine ( Pinus contorta ) decreased in basal area (18–41%), while Douglas‐fir ( Pseudotsuga menziesii ) basal area increased (21–58%). Conversely, mild warming (<2°C) coupled with greater increases in precipitation (12–13%) suggested an increase in forest cover and basal area by mid‐century, with spruce and subalpine fir increasing in abundance. Overall, we found changes in forest tree species compositions were caused by the climate‐mediated changes in fire regime (56–315% increase in annual area burned). Simulated changes in forest composition and fire regime under warming climates portray a landscape that shifts from lodgepole pine to Douglas‐fir caused by the interaction between the magnitude and seasonality of future climate changes, by climate‐induced changes in the frequency and intensity of wildfires, and by tree species response.